Manajemen Wisata Religi Masjid Menara Kudus dalam Membangun Nilai Moderasi Beragama - Ahmad, Nur; Hidayati, Nurul (PALAPA, 2026)
Studies on religious tourism in Indonesia generally focus on socio-economic dimensions and destination management, while the integration of religious tourism management with the strengthening of religious moderation values at historic sites such as Masjid Menara Kudus remains relatively limited. This study aimed to describe the management practices of religious tourism at Masjid Menara Kudus and to analyze their role in fostering religious moderation among pilgrims and local communities. A descriptive qualitative approach was employed in the Masjid Menara Kudus area, Menara Kudus, and the Tomb of Sunan Kudus, with research subjects comprising foundation managers, religious leaders, vendors, pilgrims, and local residents. Data were collected through in-depth interviews, field observations, and documentation, and were analyzed interactively through the stages of data reduction, data display, and conclusion drawing, with validity tested using source and technique triangulation. The findings show that religious tourism management at Masjid Menara Kudus is implemented by balancing the sacred function of worship, cultural preservation, and economic activities, thereby creating spiritual comfort and social order. Religious moderation values are fostered through architectural acculturation, the management of religious traditions, and socio-religious practices that emphasize tolerance and respect for differences, in line with the da‘wah legacy of Sunan Kudus. These findings affirm that religious tourism has the potential to serve as a sustainable medium for religious moderation education and provide both conceptual and practical foundations for managers and policymakers in designing governance of religious destinations that is religiously grounded and oriented toward community welfare.